DIALOGICAL INTERACTION AS A MEANS OF SOLUTION CONFLICTS IN HIGHER EDUCATION INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2022)
The given article considers the concept npedagogical conflict” in a higher school, its negative and positive functions in pedagogical interaction are examined. The author of the article emphasizes the necessity of formation at the students of dialogical interaction skills as an original mean and purpose of the decision of the pedagogical conflict.